Penerapan Gamifikasi untuk Meningkatkan Motivasi Belajar PAI di SMP 15 Kota Bengkulu - Lorenza, Diana; Istikharah, Islamiah; Rahmayanti, Novita; Wahyuda, Azi; Taufiqurrahman, Muhammad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the implementation of gamification as an innovative strategy to increase motivation to learn Islamic Religious Education (PAI) at SMP Negeri 15 Bengkulu City in the even semester of the 2024/2025 academic year. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that PAI teachers successfully integrated gamification elements such as points, badges, leaderboards, and weekly challenges into their Lesson Plans (RPP). These elements were implemented through digital platforms such as Kahoot!, Quizizz, and ClassDojo, creating an interactive and collaborative learning environment. The implementation of gamification has been proven to increase students' intrinsic motivation through healthy competition, symbolic rewards, and a fun learning environment, while also being in line with the characteristics of the digital generation. However, obstacles remain, including limited infrastructure, unequal technological literacy, and inadequate assessment supervision. Therefore, support in the form of teacher training, provision of digital resources, and student mentoring is needed. These findings can serve as a reference for educators in designing more contextual and effective PAI learning in the digital era.